High-strength flexible composite gel material, high-strength flexible strain gauge, and preparation method and application of high-strength flexible composite gel material and high-strength flexible strain gauge

By in-situ polymerization in polyurethane films to form polymers and combined with electrospinning technology, high-strength flexible composite gel materials were developed, which solved the problems of impedance mismatch and low sensitivity of traditional strain gauges, and achieved high signal-to-noise ratio and mechanical resistance Deformed strain sensing performance, suitable for health monitoring of smart wearable devices.

CN119145212APending Publication Date: 2024-12-17FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310705883.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Traditional rigid non-scalable strain gauge has problems such as impedance mismatch, narrow sensing range, imperfect fatigue resistance and low strain sensitivity in smart wearable products, which limits its application in wearable systems.

Method used

A high-strength flexible composite gel material was developed to form polymers by in-situ polymerization in polyurethane films, and an elastic polyurethane TPU fiber network was prepared using electrospinning technology, and an ionic hydrogel combining natural polymer polyvinyl alcohol and acrylamide was ionic hydrogel. , calcium chloride is introduced to improve conductivity and regulate the dynamic equilibrium of water absorption and loss of ion gels, forming a high-strength flexible strain gauges.

Benefits of technology

Achieve high signal-to-noise ratio, mechanical bending, torsion and extrusion resistance, with ultra-high break energy and fatigue thresholds, which can provide high sensing resolution and fast response over a wide response range, suitable for smart wearables Equipment health monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145212A_ABST
    Figure CN119145212A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength flexible composite gel material, a high-strength flexible strain gauge, preparation methods of the high-strength flexible composite gel material and the high-strength flexible strain gauge, and application of the high-strength flexible composite gel material and the high-strength flexible strain gauge in sensors and intelligent wearable equipment. The high-strength flexible composite gel material comprises a polyurethane film and a polymer formed by in-situ polymerization of polyvinyl alcohol-polyacrylamide-acrylic acid ion hydrogel in pores of the polyurethane film. The high-strength flexible composite gel material has excellent strain sensing performance, ultrahigh fracture energy and fatigue threshold. The high-strength flexible strain gauge obtained after photoetching has good signal-to-noise ratio and electromechanical robustness of mechanical bending resistance, torsion resistance and extrusion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a high-strength flexible composite gel material, a high-strength flexible strain gauge, a preparation method thereof, and applications in sensors and smart wearable devices, belonging to the field of smart equipment. Background Art

[0002] Traditional rigid, non-extensible strain gauges have many disadvantages that limit their practical applications, such as impedance mismatch, narrow sensing range, fragility, and fatigue / fracture resistance.

[0003] Highly stretchable strain sensors based on conductive polymer hydrogels are rapidly becoming promising candidates for various wearable skin and soft machine sensing devices. However, existing strain sensors cannot fully realize their potential when applied in wearable or robotic systems due to their inherent limitations of low stretchability and large hysteresis. In addition, strain sensors are usually susceptible to bending, torsion, and pressure deformation modes when working under unconstrained conditions. These limitations greatly hinder their practical application in soft robotic systems with large deformation ranges and multifunctionality.

[0004] In order to achieve accurate monitoring of integrated sensors while providing high stretchability, fast response and excellent repeatability in unstructured environments, many researchers are working hard to develop prototype designs of different types of sensors. Conductive polymer hydrogels have both ionic and electronic conductivity, inherent stretchability, stable conductivity, biocompatibility and mechanical robustness, and have quickly become promising candidate materials. However, most reported sensors show low signal-to-noise ratios and are greatly affected by axial external loads (bending, torsion and pressure). Therefore, high-strength flexible strain gauges with high sensing resolution in a wide response range have shown promising new functions in wearable systems. Summary of the invention

[0005] In order to solve the problems of impedance mismatch, narrow sensing range, fatigue resistance and low strain sensitivity of traditional rigid non-expandable strain gauges in current smart wearable products, according to one aspect of the present application, a high-strength flexible composite gel material and a high-strength flexible strain gauge are provided, and the high-strength flexible composite gel material has excellent strain sensing performance, ultra-high fracture energy and fatigue threshold. The high-strength flexible strain gauge obtained after photolithography has good signal-to-noise ratio and electromechanical robustness against mechanical bending, torsion and extrusion.

[0006] The high-strength flexible composite gel material comprises a polyurethane film and a polymer formed by in-situ polymerization of polyvinyl alcohol-polyacrylamide-acrylic acid ion hydrogel in the pores of the polyurethane film.

[0007] Preferably, the polyvinyl alcohol-polyacrylamide-acrylic acid ion hydrogel contains calcium chloride, a crosslinking agent and a photoinitiator.

[0008] The high-strength flexible composite gel material has a tensile strength of 8-9 MPa, an elongation at break of 1400-1600%, and a fatigue threshold of 3000-3500 J m -2 .

[0009] A high-strength flexible strain gauge is obtained by photolithography of the high-strength flexible composite gel material described above.

[0010] According to another aspect of the present application, a method for preparing the high-strength flexible composite gel material is provided. In view of the problems of impedance mismatch, narrow sensing range, fatigue intolerance and low strain sensitivity of traditional rigid non-expandable strain gauges, the inventor team of the present invention has developed a mechanical interlocking strategy to integrate elastomers and ionic hydrogels in the material. Specifically: an elastic polyurethane TPU fiber network with high elasticity and structural deformability is prepared by electrospinning technology; at the same time, an ionic hydrogel of natural polymers polyvinyl alcohol (PVA) and polyacrylamide (PAM) / acrylic acid (AA) is constructed. During the research process, the inventors found that the introduction of calcium chloride can not only provide good conductivity but also regulate the dynamic balance of water absorption and loss of the ionic gel to achieve a long-term stable effect. The ionic hydrogel is then infiltrated into the TPU substrate, and the polymerization is initiated under ultraviolet light in the original polymerization manner to prepare the TPU composite ionic gel.

[0011] The method for preparing the high-strength flexible composite gel material comprises the steps of infiltrating a solution containing polyvinyl alcohol, acrylamide and acrylic acid into the pores of a polyurethane film, and performing light curing to obtain the high-strength flexible composite gel material.

[0012] As a specific implementation, the method for preparing the high-strength flexible composite gel material comprises the following steps:

[0013] a) adding acrylamide to a polyvinyl alcohol aqueous solution, then adding calcium chloride, and after dissolving, adding acrylic acid, a crosslinking agent and a photoinitiator to obtain a solution A;

[0014] b) preparing a polyurethane elastic film by using electrospinning technology;

[0015] c) dripping the solution A obtained in step a) into the polyurethane elastic film obtained in step b), and after the solution A penetrates the polyurethane elastic film, placing it under ultraviolet light for photocuring to obtain a high-strength flexible composite gel material.

[0016] Preferably, the weight percentage of polyvinyl alcohol in the solution A in step a) is 0.5-1.5wt%;

[0017] The weight percentage of acrylamide is 10-20wt%;

[0018] The weight percentage of CaCl2 is 15-25wt%;

[0019] The weight percentage of acrylic acid is 1.5 to 7.5 wt %;

[0020] Cross-linking agent: 0.01-0.02 wt%;

[0021] Photoinitiator: 0.6~1.0wt%.

[0022] Further preferably, the weight percentage of polyvinyl alcohol in the solution A in step a) is 0.8-1.2 wt %;

[0023] The weight percentage of acrylamide is 15-20wt%;

[0024] The weight percentage of CaCl2 is 18-23wt%;

[0025] The weight percentage of acrylic acid is 2.4-6.0wt%;

[0026] Cross-linking agent: 0.01-0.02 wt%;

[0027] Photoinitiator: 0.6~1.0wt%.

[0028] More preferably, the weight percentage of polyvinyl alcohol in the solution A in step a) is 1 wt %;

[0029] The weight percentage of acrylamide is 16wt%;

[0030] The weight percentage of CaCl2 is 20wt%;

[0031] The weight percentage of acrylic acid is 4wt%;

[0032] Cross-linking agent: 0.016wt%;

[0033] Photoinitiator: 0.8 wt%.

[0034] Preferably, the cross-linking agent is N,N'-methylenebisacrylamide.

[0035] Preferably, the photoinitiator is at least one of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (photoinitiator 2959), 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator 1173) or 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone (photoinitiator MBF).

[0036] Preferably, step b) is: preparing the polyurethane elastic film from a solution containing polyurethane using an electrospinning process;

[0037] The solution containing polyurethane is a tetrahydrofuran and N,N'-dimethylformamide solution of polyurethane.

[0038] Preferably, in the solution containing polyurethane, the weight percentage of the solute polyurethane is 15-25wt%.

[0039] Optionally, the polyurethane particles are added to a mixed solution of tetrahydrofuran (TNF) and N,N-dimethylformamide (DMF), mixed and stirred at room temperature for 10 to 15 hours to obtain the solution containing polyurethane.

[0040] Preferably, in the solution containing polyurethane, the solvent is a mixed solvent consisting of tetrahydrofuran and N,N'-dimethylformamide, and the volume ratio of tetrahydrofuran to N,N'-dimethylformamide is 4-5:1.

[0041] Preferably, the conditions of the electrospinning process are: the temperature during electrospinning is 60-80° C., and the distance between the needle tip and the collector is 14-18 cm.

[0042] Optionally, the temperature during electrospinning is independently selected from 60°C, 70°C, and 80°C.

[0043] Optionally, the distance between the needle tip and the collector is independently selected from 14 cm, 15 cm, 16 cm, 17 cm, 18 cm.

[0044] Preferably, in step c), the polyurethane elastic film is firstly plasma cleaned and then the solution A is dripped into it.

[0045] Preferably, in step c), photocuring is performed under ultraviolet light, the distance between the ultraviolet light source and the polymer is 5 to 10 cm, and the illumination time is 0.5 to 1 h.

[0046] According to another aspect of the present application, there is provided application of the high-strength flexible composite gel material and the high-strength flexible strain gauge in a sensor.

[0047] According to another aspect of the present application, there is provided an application of the high-strength flexible composite gel material and the high-strength flexible strain gauge in a smart wearable device, and the smart wearable device can be used for human health monitoring.

[0048] In the present application, polyvinyl alcohol is abbreviated as PVA, polyacrylamide is abbreviated as PAM, acrylic acid is abbreviated as AA, polyurethane is abbreviated as TPU, tetrahydrofuran is abbreviated as TNF, and N,N-dimethylformamide is abbreviated as DMF.

[0049] The beneficial effects of this application include but are not limited to:

[0050] (1) The high-strength flexible composite gel material provided in the present application has good biocompatibility and is a healthy, non-toxic, harmless and degradable material, which can be used in the fields of biological tissue monitoring and medical health.

[0051] (2) The high-strength flexible composite gel material provided in the present application has excellent stability and can be stored for a long time without any protective measures, and water loss and water absorption can reach a dynamic balance.

[0052] (3) The high-strength flexible composite gel material provided in this application has a mechanical interlocking structure of ion gel and elastomer network, which makes it have a strength of 59.6 kJ m -2 Ultra-high fracture energy and 3300J m -2 fatigue threshold while maintaining excellent strength and tensile properties.

[0053] (4) The high-strength flexible composite gel material provided in the present application has excellent strain sensing performance under static and dynamic loading, with a tiny detection limit (0.05% strain), an ultrafast response time (0.495ms), while maintaining high linearity.

[0054] (5) The high-strength flexible composite gel material provided in this application can accurately detect human body-related frequency vibrations in the full range of 0.5-1000 Hz and realize the measurement of physiological parameters.

[0055] (6) The high-strength flexible strain gauge provided in this application has a good signal-to-noise ratio and electromechanical robustness against mechanical bending, torsion and extrusion.

[0056] (7) By integrating multiple high-strength flexible strain gauges provided in this application through a multi-channel acquisition device, an intelligent human motion detection system can be constructed. The system can classify typical human motions with the assistance of machine learning technology. This innovation will promote the development of wearable telemedicine technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 It is a schematic diagram of the preparation of the high-strength flexible strain gauge provided in this application.

[0058] Figure 2 The high-strength flexible strain gauge 1 obtained in Example 1 # Environmental stability test results.

[0059] Figure 3 The high-strength flexible composite gel material 1 obtained in Example 1 # Fracture energy and fatigue threshold test results; Figure 3 (a) is the fracture energy of the material; Figure 3 (b) is the fatigue threshold of the material.

[0060] Figure 4 The high-strength flexible composite gel material 1 obtained in Example 1 # The sensor performance test results; Figure 4 (a) Flexible material sensitivity factor and linearity; Figure 4 (b) is the response characteristic of the material to small strain; Figure 4 (c) is the response time of the material under dynamic load.

[0061] Figure 5 The high-strength flexible composite gel material 1 obtained in Example 1 # Accurately detect the full range of human-related frequency vibration results between 0.5-1000Hz; Figure 5 (a) is the response characteristics of the composite material at different vibration frequencies; Figure 5 (b) is the Fourier transform spectrum at different vibration frequencies.

[0062] Figure 6 The high-strength flexible strain gauge 1 obtained in Example 1 # The electromechanical robustness test results against mechanical bending, torsion and extrusion; Figure 6 (a) The electromechanical robustness of the flexible strain gauge to bending; Figure 6 (b) The electromechanical robustness of the flexible strain gauge to torsion; Figure 6 (c) The electromechanical robustness of the flexible strain gauge to compression.

[0063] Figure 7 The multi-channel high-strength flexible strain gauge 1 obtained by Example 1 is collected # Sensor data,build a high-precision neural network model for whole-body motion classification. DETAILED DESCRIPTION

[0064] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0065] Unless otherwise specified, the raw materials and reagents used in this application were purchased from commercial sources and used directly without treatment. The instruments and equipment used adopted the schemes and parameters recommended by the manufacturers.

[0066] Figure 1 This is a schematic diagram of the strategy used in the preparation of high-strength flexible strain gauges in this application. Specifically:

[0067] Utilizing the resistance sensing mechanism of commercial strain gauges, a flexible strain gauge with conductive elements of a specific structure was fabricated to enhance the strain gauge's ability to respond to loads in a specific direction.

[0068] Example 1 High-strength flexible composite gel material 1 # , High strength flexible strain gauge 1 # Preparation

[0069] (1) 0.25 g of polyvinyl alcohol (PVA) having a degree of polymerization of 1799 was added to 14.55 ml of deionized water, which was placed in a 95°C oil bath and heated with stirring for 0.5 h. 4 g of acrylamide was then added thereto and stirred for 0.5 h. 5 g of calcium chloride was then slowly added to the mixed solution in batches. After all components were dissolved and stirred evenly, 1 g of acrylic acid, 0.004 g of N,N'-methylenebisacrylamide and 0.2 g of photoinitiator 2959 were added to the mixed solution and stirred for 1 h to obtain Solution 1.

[0070] (2) 1.9 g of polyurethane particles were added to a mixed solution of 2 ml of dimethylformamide and 8 ml of tetrahydrofuran, and stirred on a magnetic stirring table at room temperature for 10 hours to form a uniform and transparent solution, which was then prepared into a polyurethane elastic film with a thickness of 0.1 cm by an electrospinning machine. During the preparation process, the spinning machine injection speed was 0.17 ml / min, the distance between the needle tip and the collector was set to 16 cm; and the temperature was 70°C.

[0071] (3) After the polyurethane elastic film is cleaned in a plasma cleaning machine, the solution 1 obtained in step (1) is dropped into the polyurethane elastic film to make it penetrate into the pores of the film, and then the film permeated with the solution is placed under ultraviolet light for photocuring; the distance between the ultraviolet light source and the film is 8 cm, and the photocuring time is half an hour, thereby obtaining a high-strength flexible composite gel material 1 # .

[0072] (4) Using the American ABM lithography machine, the material obtained in (3) is processed into the shape of a uniaxial strain gauge, thus obtaining the high-strength uniaxial flexible strain gauge, which is denoted as 1 # .

[0073] Example 2 High-strength flexible composite gel material 2-5 # , High strength flexible strain gauge 2 # ~5 # Preparation

[0074] The preparation steps are the same as those in Example 1. On the basis of Example 1, the high-strength flexible composite gel materials 2-5 are obtained according to the parameter adjustment conditions in Table 1. # , High strength flexible strain gauge 2 # ~5 # .

[0075] Table 1

[0076]

[0077]

[0078] Example 3 Water retention test

[0079] Using the natural evaporation method, the sample high-strength flexible strain gauge 1 # ~5 # The water retention rate of the strain gauge was tested. The results show that the high-strength flexible strain gauge obtained in this application not only has a high water retention rate (about 1.0), but is also very stable.

[0080] Sample high strength flexible strain gauge 1 # is a typical representative, and the test results of its water retention rate are as follows Figure 2 As shown. Figure 2 It can be seen that the water retention rate of the high-strength flexible strain gauge obtained in the present application is stable at about 1.0 after 25 days.

[0081] Example 4 Fracture Energy and Fatigue Threshold Test

[0082] The Greensmith method was used to test the high-strength flexible composite gel material 1 on a universal material testing machine. # ~5 # The fracture energy and fatigue threshold of the composite gel material were tested. The results showed that the tensile strength of the high-strength flexible composite gel material obtained in this application was 8-9 MPa, the elongation at break was 1400-1600%, and the fatigue threshold was 3000-3500 J m -2 .

[0083] Sample high strength flexible composite gel material 1 # is a typical representative, and the test results of its fracture energy and fatigue threshold are as follows Figure 3 As shown. It can be seen that the material has excellent mechanical properties.

[0084] Example 5 Sensing performance test

[0085] Using a universal material testing machine and a high-precision digital source meter device, the sample high-strength flexible composite gel material 1 # ~5 # The strain sensitivity and detection limit were tested.

[0086] The results show that the high-strength flexible composite gel material obtained in the present application has excellent strain sensing performance, with a small detection limit (0.05% strain), an ultra-fast response time (0.495ms), and also maintains high linearity.

[0087] Sample high strength flexible composite gel material 1 # As a typical representative, the test results of its sensing performance are as follows Figure 4As shown in Figure 2, it can be seen that the material exhibits excellent linearity and can respond to tiny strains in a very short time.

[0088] Example 6 Human body related frequency vibration test

[0089] On the vibration test bench, the sample high-strength flexible composite gel material 1 # ~5 # The full range of human body-related frequency vibrations between 0.5-1000 Hz was tested. The results show that the high-strength flexible composite gel material obtained in the present application can accurately detect the full range of human body-related frequency vibrations between 0.5-1000 Hz and achieve the measurement of physiological parameters.

[0090] Sample high strength flexible composite gel material 1 # is a typical representative, and the test results of its frequency and amplitude are as follows Figure 5 As shown in Figure 2, it can be seen that the material can accurately respond to the vibration frequencies related to human body movements.

[0091] Based on the above test results, the multi-channel high-strength flexible strain gauge 1 obtained in Example 1 was collected. # Sensor data, build a high-precision neural network model for whole-body motion classification, see Figure 7 .

[0092] Example 7 Signal-to-noise ratio and mechanical bending, torsion and compression resistance tests

[0093] On the flexible electronic test platform, the sample high-strength flexible strain gauge 1 # ~5 # The signal-to-noise ratio and electromechanical robustness against mechanical bending, torsion and extrusion were tested. The results show that the high-strength flexible strain gauge obtained in this application has excellent strain sensing performance, good signal-to-noise ratio and electromechanical robustness against mechanical bending, torsion and extrusion.

[0094] Sample high strength flexible strain gauge 1 # As a typical representative, the test results of its sensing performance are as follows Figure 6 shown.

[0095] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A high-strength flexible composite gel material, characterized in that: The invention comprises a polyurethane film and a polymer formed by in-situ polymerization of polyvinyl alcohol-polyacrylamide-acrylic acid ion hydrogel in the pores of the polyurethane film.

2. The high-strength flexible composite gel material according to claim 1, characterized in that: The polyvinyl alcohol-polyacrylamide-acrylic acid ion hydrogel contains calcium chloride, a crosslinking agent and a photoinitiator.

3. The high-strength flexible composite gel material according to claim 1, characterized in that: The high-strength flexible strain gauge has a tensile strength of 8-9 MPa, a breaking elongation of 1400-1600%, and a fatigue threshold of 3000-3500 J m -2 .

4. A high-strength flexible strain gauge, characterized in that: The high-strength flexible composite gel material according to any one of claims 1 to 3 is obtained by photolithography.

5. The method for preparing the high-strength flexible composite gel material according to any one of claims 1 to 3, characterized in that: The method comprises the steps of infiltrating a solution containing polyvinyl alcohol, acrylamide and acrylic acid into the pores of a polyurethane film, and then performing light curing to obtain the high-strength flexible composite gel material.

6. The method according to claim 5, characterized in that The following steps are involved: a) adding acrylamide to a polyvinyl alcohol aqueous solution, then adding calcium chloride, and after dissolving, adding acrylic acid, a crosslinking agent and a photoinitiator to obtain a solution A; b) preparing a polyurethane elastic film by using electrospinning technology; c) dripping the solution A obtained in step a) into the polyurethane elastic film obtained in step b), and after the solution A penetrates the polyurethane elastic film, placing it under ultraviolet light for photocuring to obtain the high-strength flexible composite gel material.

7. The method according to claim 6, characterized in that The weight percentage of polyvinyl alcohol in the solution A in step a) is 0.5-1.5wt%; The weight percentage of acrylamide is 10-20wt%; The weight percentage of CaCl2 is 15-25wt%; The weight percentage of acrylic acid is 1.5 to 7.5 wt %; Cross-linking agent: 0.01-0.02 wt%; Photoinitiator: 0.6-1.0wt%; Preferably, the weight percentage of polyvinyl alcohol in the solution A in step a) is 1wt%; The weight percentage of acrylamide is 16wt%; The weight percentage of CaCl2 is 20wt%; The weight percentage of acrylic acid is 4wt%; Cross-linking agent: 0.016wt%; Photoinitiator: 0.8wt%; Preferably, the cross-linking agent is N,N'-methylenebisacrylamide; Preferably, the photoinitiator is at least one of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone.

8. The method according to claim 6, characterized in that Step b) is: preparing the polyurethane elastic film from a solution containing polyurethane using an electrospinning process; The solution containing polyurethane is a solution of polyurethane in tetrahydrofuran and N,N'-dimethylformamide; Preferably, in the solution containing polyurethane, the weight percentage of the solute polyurethane is 15 to 25 wt%; Preferably, in the solution containing polyurethane, the solvent is a mixed solvent consisting of tetrahydrofuran and N,N'-dimethylformamide, and the volume ratio of tetrahydrofuran to N,N'-dimethylformamide is 4 to 5:1; Preferably, the conditions of the electrospinning process are: the temperature during electrospinning is 60-80° C., and the distance between the needle tip and the collector is 14-18 cm; preferably, in step c), the polyurethane elastic film is first plasma cleaned and then the solution A is dropped into it.

9. Use of the high-strength flexible composite gel material according to any one of claims 1 to 3 and the high-strength flexible strain gauge according to claim 4 in a sensor.

10. Application of the high-strength flexible composite gel material according to any one of claims 1 to 3 and the high-strength flexible strain gauge according to claim 4 in smart wearable devices.

Citation Information

Patent Citations

  • Preparation method and application of aqueous solid electrolyte

    CN113012947A

  • Flexible fabric / gel composite material and preparation method and application thereof

    CN116043548A

  • Multifunctional hydrogel-web composites for enhanced absorbency applications and methods of making the same

    US20080057811A1